A comparative study on anaerobic treatment between ponding system and digester tank system for palm oil mill effluent (POME) treatment - Intan Safinaz, Ismail (2010)
Palm oil is one of the important industrial sectors in Malaysia.Every year,the production of palm oil increased rapidly.As the production of palm oil increased, more palm oil mill effluent(POME)is generated annually.The total annual quantity of wastewater generated is estimated to be 1.8×106m3.This situation contributed to more study on the technology of treatment of the POME.Raw POME comprises of water-soluble components of the palm fruits as well as some suspended materials like palm fibre and oil and it cannot be discharged into the watercourse directly.The effluent must be treated to acceptable quality before it can be discharged.Comparison on conventional system and alternative system for anaerobic treatment between ponding system and digestion tank treatment system was used for treatment POME. The resources of this data are taken from the selected Palm oil Mill Plantations.The main parameters for POME are BOD, COD, Suspended Solid,and Oil & Grease.The reduction of main parameters for Ponding System and Digester Tank System was determine which is BOD, 96.88% and 98.06%,COD,90.60% and 92.70%,SS,94.03% and 96.83% and O&G,97.21% and 81.33%. Meanwhile,the quality,effectiveness and the advantages and disadvantages for both systems also were determined.The findings show that alternative treatment system which is Digester Tank System having efficiency, effective and ability to treat POME better than conventional treatment system.